Exploring Photovoice in Digital Storytelling for English Language Learning: A New Frontier in Language Acquisition - Handayani, Indah; Pradana, Dian Arief (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
This article investigates Photovoice as a potentially transformative approach to digital storytelling within the context of English language education. Situated within the broader framework of seeking innovative pedagogical approaches that cultivate both linguistic proficiency and critical engagement, the study aims to ascertain how Photovoice, a participatory visual methodology, can enhance learners' communicative competence, narrative abilities, and intercultural understanding. Employing a qualitative research methodology grounded in a comprehensive review of existing literature on digital storytelling, Photovoice, and language learning, this article analyzes the pedagogical implications of this approach. Findings suggest that Photovoice empowers learners through creative self-expression, strengthens visual literacy, and facilitates the development of sophisticated English language skills. While the findings robustly support the potential of Photovoice, the review also acknowledges limitations within the existing research corpus. The conclusion posits that Photovoice offers a valuable and engaging pedagogical tool for enriching the language learning environment and promoting deeper learning outcomes. This article further emphasizes the significance of integrating technology into language education through the implementation of Photovoice. By utilizing digital platforms for sharing and showcasing visual narratives, learners are empowered to articulate their thoughts and experiences, thereby engaging with a wider audience beyond the confines of the classroom. Ultimately, this approach not only enhances language skills but also promotes empathy and global citizenship among learners, making it a multifaceted tool for contemporary education.